Interprofessional Collaboration And Its Association With Patient Safety Practices Among Laboratory, Nursing, And Radiology Professionals In Saudi Arabia: A Cross-Sectional Study (The Review of Diabetic Studies, 2025)
Background: Interprofessional collaboration (IPC) is recognized as a critical determinant of patient safety and quality of care in healthcare systems. While evidence suggests that collaborative practices among healthcare professionals improve outcomes, limited research exists on the relationship between IPC and patient safety among laboratory, nursing, and radiology professionals in Saudi Arabia.This study aimed to examine the association between IPC and patient safety practices across these disciplines.Methods: A cross-sectional study was conducted among 420 healthcare professionals (nursing 180; laboratory 140; radiology 100) working in public and private hospitals in Saudi Arabia. Data were collected using a structured, self-administered questionnaire assessing interprofessional collaboration and patient safety practices, with validated 5-point Likert scales. Descriptive statistics summarized participant characteristics and scale scores. Inferential analyses included ANOVA, t-tests, Pearson correlation, and multiple linear regression to identify predictors of patient safety practices.Results: Participants reported moderate to high levels of IPC (Mean ± SD = 3.84 ± 0.62) and patient safety practices (4.01 ± 0.58). Nurses demonstrated significantly higher IPC and safety scores compared to laboratory and radiology professionals (p = 0.032). Significant associations were observed between patient safety practices and profession, age, years of experience, and work setting (p < 0.05). A strong positive correlation was found between IPC and patient safety practices (r = 0.62, p < 0.001). Multiple linear regression indicated that IPC was the strongest predictor of patient safety practices (β = 0.51, p < 0.001), explaining 46% of the variance in safety outcomes.Conclusion: Interprofessional collaboration is strongly associated with patient safety practices among laboratory, nursing, and radiology professionals in Saudi Arabia. Nurses reported the highest collaboration and safety scores, while years of experience and work setting further influenced safety performance. These findings highlight the need for interprofessional education, structured teamwork training, and inclusive organizational policies to enhance collaborative practice and improve patient safety across healthcare disciplines.